Case Report: A Protracted Journey to Diagnosis of Systemic Sclerosis – A Call for Enhanced Clinical Vigilance - Sana Abbas (Utan Kayu Publishing, 2026)
To illustrate features of diagnostic delay in systemic sclerosis (SSc) and underscore the value of multisystem integration in primary care. It also highlights cognitive and system factors that prolong recognition of rare autoimmune disease in resource-limited settings, including delayed referral. A 37-year-old female healthcare professional in Pakistan underwent a 13-year diagnostic odyssey marked by persistent xerosis/photosensitivity, recurrent ectopic pregnancies, Raynaud’s phenomenon, profound weight gain, fatigue, and later inflammatory symptoms. Severe COVID-19 (Delta variant) in July 2021 precipitated acute hypoxemic respiratory failure and prompted imaging that revealed interstitial lung disease (ILD). Autoimmune testing showed antinuclear antibodies (ANA) 1:320 with a nucleolar pattern and anti–topoisomerase I (anti–Scl-70) positivity. High-resolution computed tomography demonstrated bilateral basal ground-glass opacities with traction bronchiectasis consistent with a non-specific interstitial pneumonia (NSIP) pattern, supporting SSc-associated ILD. The patient was started on mycophenolate mofetil (2 g/day) with a tapering course of prednisolone, leading to clinical stabilization and preserved pulmonary function on follow-up. Persistent Raynaud’s phenomenon with subtle skin changes should trigger early ANA screening; recurrent obstetric complications may signal systemic vasculopathy; and anchoring bias can delay diagnosis when symptoms are treated in isolation rather than as a unified syndrome.